Studi Literatur Pola Makan dan Pola Aktivitas Fisik pada Remaja dengan Obesitas di Indonesia - Purnomo, Wahyu; Susanto, Tantut; Afandi, Alfid Tri (UPT Percetakan dan Penerbitan Universitas Jember, 2024)
The nutritional problem in Indonesia in modern times is still complex. One of them is obesity that can occur in children, adolescents, and adults. Obesity can be caused by technological developments and consumption patterns of fast food, which is a lifestyle that causes a decrease in physical activity. This literature aims to describe the diet and physical activity patterns that cause obesity. The sources of journals/ articles used in the search for relevant databases were obtained through PubMed, Science Direct, Sinta, and Google Scholar with the 2015-2020 publication years and were traced using a combination of search terms for adolescent diet, adolescent obesity, and adolescent activity patterns. Then, it was analyzed using the PRISMA diagram method with four stages, namely identification, screening, feasibility, and insertion. This review identified that adolescents have a poor diet and often do light physical activity which causes obesity due to frequent consumption of fast food, high fat, high protein, and carbohydrates, eating at nighttime and excessive portions, not eating breakfast, often doing light activities such as watching tv, mopping and others and rarely exercising. The conclusion is that the energy coverage both the frequency, type, and amount needed with physical activity, both light, moderate and heavy, still needs to be studied more deeply. The importance of imparting nutritional knowledge in early childhood so that they can support life in the future.